1999
DOI: 10.1016/s0896-6273(00)80682-0
|View full text |Cite
|
Sign up to set email alerts
|

Control of Neuronal Precursor Proliferation in the Cerebellum by Sonic Hedgehog

Abstract: Cerebellar granule cells are the most abundant type of neuron in the brain, but the molecular mechanisms that control their generation are incompletely understood. We show that Sonic hedgehog (Shh), which is made by Purkinje cells, regulates the division of granule cell precursors (GCPs). Treatment of GCPs with Shh prevents differentiation and induces a potent, long-lasting proliferative response. This response can be inhibited by basic fibroblast growth factor or by activation of protein kinase A. Blocking Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
1,055
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,236 publications
(1,103 citation statements)
references
References 76 publications
44
1,055
0
4
Order By: Relevance
“…In the SHH subtype is established that granule cell progenitors (GCPs) represent the cell of origin of the malignancy (Wechsler‐Reya & Scott, 1999; Marino et al , 2000; Oliver et al , 2005; Schuller et al , 2008). Thus, we tested the effect of siRNA and the expression of Fbxl17 in GCPs.…”
Section: Resultsmentioning
confidence: 99%
“…In the SHH subtype is established that granule cell progenitors (GCPs) represent the cell of origin of the malignancy (Wechsler‐Reya & Scott, 1999; Marino et al , 2000; Oliver et al , 2005; Schuller et al , 2008). Thus, we tested the effect of siRNA and the expression of Fbxl17 in GCPs.…”
Section: Resultsmentioning
confidence: 99%
“…Shh could be controlling proliferation by inducing FGF signaling and subsequently activating cyclin genes indirectly. However, it is also possible that Shh may have an FGF-independent role in regulating cell cycle progression, since it has been demonstrated that Shh is able to regulate key cyclin genes or other important cell cycle regulators, including phosphatases in different contexts (Dahmane and Ruiz i Altaba, 1999;Wallace, 1999;Wechsler-Reya and Scott, 1999;Kenney and Rowitch, 2000;Barnes et al, 2001;Kenney et al, 2003;Oliver et al, 2003;Cayuso et al, 2006;Yu et al, 2006). Recent evidence from studies in the mouse retina have shown that activation of the Hh pathway acts in a cellautonomous manner to up-regulate cyclinD1 and increase progenitor cell proliferation (Yu et al, 2006).…”
Section: Fgf and Shh Display Proliferative Effects During Retina Regementioning
confidence: 99%
“…However these early studies did not distinguish between the stem and progenitor cell populations (including both transit amplifying cells and neuroblasts), and subsequent studies of the EGF-induced proliferation in the SEZ suggest that it is the transit amplifying cells that are responsive to the EGF (Doetsch et al, 2002). Shh is a wellestablished mitogen for granule cell precursors (Wechsler-Reya and Scott, 1999), and also promotes stem/precursor cell proliferation and increases proliferation in the SEZ (Palma and Ruiz i Altaba, 2004). Here, a recent cell marking study using expression of lacZ in the R26R reporter mouse, activated by expression of Cre recombinase driven by the Shh-target Gli1, showed directly that the Shh-responsive cell population includes both neural stem cells and transit amplifying cells (Ahn and Joyner, 2005).…”
Section: Signaling In Adult Neural and Other Stem Cell Nichesmentioning
confidence: 99%